Ambiguity in Hezekiah’s Last Words in Isaiah 39:8 - Campbell, Nicholas J. (Biblische Zeitschrift, 2025)
In this article, we argue that the author of Isaiah 39:8b wrote Hezekiah’s final speech, “there will be peace and truth in my days”, in an ambiguous manner. The effect of this ambiguity is doubt in the reader’s mind about Hezekiah. Not only is Hezekiah’s piety questionable, but the syntactical relationship of his speech to the narrative is ambiguous. We show this first by a discussion of the syntax of the parallel passage in 2 Kings 20:19. This is followed by a discussion of the function of initial כי clauses in reported speech within the Hebrew Bible to identify the common categories of usage. Then Isaiah 39:8b is discussed in relation to these categorizations. Finally, Isaiah 39:8 is compared to Isaiah 38:22 to show how Hezekiah’s speech ends both narratives with unclear syntactical and theological connections to the speeches immediately preceding them.